Deletion of 11 Amino Acids in p90(rsk-mo-1) Abolishes Kinase Activity - Spring, Denise J. (American Society for Microbiology, 1999)
p90(rsk) is a distal member of the mitogen-activated protein kinase signaling pathway. It has been cloned from a variety of species including Xenopus laevis, mouse, chicken, rat, and human. The clone p90(rsk-mo-1), isolated by others from a mouse library, contains a unique 33-nucleotide deletion not found in the p90(rsk) clones from any other species that have been examined. When p90(rsk-mo-1) was expressed in Cos-7 cells that were subsequently stimulated with epidermal growth factor, the immunoprecipitated p90(rsk-mo-1) protein showed no measurable kinase activity toward the ribosomal protein S6 peptide. By comparison, expression of rat p90(rsk-1) resulted in significant kinase activity. Deletion of the 33-nucleotide region missing in the p90(rsk-mo-1) clone from the p90(rsk-rat-1) cDNA abolished kinase activity in the resulting protein. When these 33 nucleotides were introduced into the p90(rsk-mo-1) cDNA, the expressed protein showed significant kinase activity. Reverse transcription-PCR and direct sequencing of mRNA isolated from several mouse tissues indicated the presence of the full-length form of p90(rsk-1) in the mouse and showed no conclusive evidence for a deletion-containing form. This study indicates the presence of a full-length p90(rsk-1) mRNA in mouse tissues that is homologous to that identified in other species and suggests that the deletion in p90(rsk-mo-1) may be a cloning artifact. The findings provide additional support for the conclusion that the first catalytic domain of p90(rsk) is responsible for its enzymatic activity toward ribosomal protein S6.